Pengembangan Media KOKIPAS Berbasis Canva untuk Meningkatkan Keterampilan Membaca Siswa Kelas IV - Nurul Haliza Lubis; Muhammad Noer Fadlan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to develop a learning media called KOKIPAS (Creative Comic of IPAS) based on Canva, focusing on the topic Plants, the Source of Life on Earth, to enhance the reading skills of fourth-grade students at SDN 067775 Medan Johor. The research employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), which consists of five systematic stages for instructional media development. The objective of the study is to determine the validity, effectiveness, practicality, and the capability of the KOKIPAS media in improving students' reading skills. Validation was conducted by four experts, including a media expert, a subject matter expert, a teaching module expert, and a classroom teacher. The validation results indicated that KOKIPAS media achieved an average validity percentage of 89.61%, categorized as very valid and feasible for use. In terms of effectiveness, the evaluation results showed that the student response questionnaire scored 90.14% (strongly agree), and the reading skills test scored 86% (very good), resulting in an average effectiveness score of 88.07%, which falls into the effective category. Regarding practicality, the instructional media questionnaire scored 4.67%, classified as very practical. The improvement in students’ reading skills also showed significant results. Out of 28 students, the majority achieved an improvement percentage above 80%, with an overall average of 88.07%. This indicates that the KOKIPAS media is effective in helping students understand the material through a visual and narrative approach. Therefore, the Canva-based KOKIPAS media is declared valid, effective, practical, and capable of enhancing students’ reading skills, making it a suitable alternative learning medium for IPAS subjects in elementary schools.